The Ellipse of Position Error - Mohammed Anwer Jassim (Zanco journal of pure and applied sciences, 2019)
The uncertainty of the measured points (positions) takes a prominent place in many of the researches that concern the surveying and geomatics issues. The definition of the shape and the orientation of ellipse of position error for the points were the main subjects of those works. However, two methods are mostly used for calculating the size, and the direction of the error ellipse. First one involves the two dimensional rotation issue, and the second concerns the eigenvalues problem. The basic idea behind this research is to evaluate these methods (mentioned above) according to the validation of the obtained results and highlight the effect of the coordinate’s correlation on the size and the direction of the ellipse of position error.